النحو العربي و أثره في التفسير القرآني = Arabic grammar and its role in Quranic interpretation - Alhamdi, Sulaiman Abdullah Salim Said; Ali, Asem Shehadeh Saleh; Ismail, Yasir; Salleh, Abdul Halim (SIATS, 2021)
The Arabic language is the receptacle of the Noble Qur’an, which I was honored to have, and gained from its immortality and survival until the Day of Resurrection, unlike other languages. And whoever wants to interpret the Noble Qur’an must be familiar with the Arabic language and its sciences, especially the grammar of the Arabic language. Because the meaning changes and varies according to the different syntax, and our study here is concerned with one of the branches of the Arabic language, which is grammar. The problem of our study is: What is the effect of Arabic grammar on Quranic interpretation? Does the difference in the parsing lead to a different interpretation? Therefore, we adopted the descriptive analytical approach. This study aims to: Clarify the relationship between grammar and interpretation, the extent of the need for grammatical expression in Qur’anic interpretation, and the effect of differences in Qur’anic grammar on meaning with applied examples. The study concluded with a number of results, the most prominent of which are: that the rules help in the correct understanding of the meanings of the noble verses, and that different parsing leads to a difference in the meanings of the verses